Do bioactive carotenoids contribute to the color of edible mushrooms? - Ribeiro, Bárbara (2012)
Carotenoids are biologically active phytochemicals present as micro-components in fruits and vegetables, being responsible for their yellow, orange and red colors. The chromatographic behavior and the UV absorption spectrum provided by HPLC-DAD analysis constitute the clues for their identification. Mushrooms are of increasing importance in modern nutrition and medicine, due to the presence of metabolites with pharmacological potential. In this work, samples of wild and commercial mushroom species (Agaricus bisporus, Amanita caesarea, Amanita rubescens, Boletus edulis, Cantharellus cibarius, Fistulina hepatica, Hydnum rufescens, Hygrophorus agathosmus, Pholiota nameko, Pleurotus ostreatus, Russula cyanoxantha, Suillus bellini, Suillus bovinus, Suillus granulatus, Suillus luteus, Tricholoma equestre and Tricholoma portentosum) were screened by HPLC-DAD for the presence of carotenoids. By applying this methodology to 22 samples, comprising either lyophilized or fresh materials, only β-carotene was found and just in C. cibarius species. The occurrence of this pigment in other three of the analyzed species previously described raises some questions about the methodology used.